Analysis of the risk of liquidation depending on the age of the company: a study of entities established in Szczecin in period 1990-2010 - Markowicz, Iwona (Analiza ryzyka likwidacji w zależności od wieku firmy na przykładzie podmiotów powstałych w Szczecinie w latach 1990-2010, 2019)
The aim of the research was an assessment of the relative risk of liquidation of a company depending on its age. The research covered economic entities established in Szczecin in the period 1990-2010. The analysis was carried out with the use of a logit model. The risk of company liquidation was examined depending on the entity’s age expressed both in months (continuous variable) and in grouped intervals (year, half-year). In this way, attention was drawn to the benefits of continuous variable coding (rank and 0-1 coding). The research covered companies established during 1990-2010 in total (over 120 thousand) and in time periods resulting from the cyclical character of liquidation of companies (in accordance with the earlier research findings). The research showed that the risk of company liquidation decreases as the company grows older (the use of a continuous variable and a rank variable). On the other hand, the risk of subsequent age groups (using the 0-1 variable) prevents the risk from being monotonous
Econometrics = Ekonometria, 2019, Vol. 23, No. 2, s. 49-62
Keywords: survival analysis; firms duration; risk of liquidation; analiza przeżycia; trwanie firm; ryzyko likwidacji